Religious existentialists about the phenomenon of the crisis - S. H. Karpova (Granì, 2014)
The article revealed the basic situation of the phenomenon of crisis in the religious existentialism. Philosophers of religious existentialism (Buber, Marcel, Jaspers) was analyzed the phenomenon of the crisis primarily through anthropological topic. Anthropological crisis in philosophy Buber and Marcel was revealed by analyzing the relationship between man and God. A possible way out of the crisis – it is an interpersonal dialogue between God and man («I – You»). M. Buber distinguishes sociological nature of the crisis and the crisis of the spirit. It focuses attention on the relationship «loneliness – a crisis». Analyzing contemporary anthropological crisis, he associates it with the theme of technological progress and decline of spirituality. So the philosopher comes to clarify three areas of human life, which manifests itself through the crisis of the human soul. There is such area of life: technology, economy and political practice. They, said M. Buber, formed in the human soul loneliness and emptiness. Marcel and Jaspers also drew attention to the problem of the relationship of «man – machinery». They noted the influence of the existence of such a relationship crisis and decline in spirituality.